Occult tethered cord syndrome: insights into clinical and MRI features, prognostic factors, and treatment outcomes in 30 dogs with confirmed or presumptive diagnosis - Espinosa Romero, Javier; De Decker, Steven; Santifort, Koen; Gutierrez-Quintana, Rodrigo; Ortega, Maria; Uriarte, Ane; Mojarradi, Abtin; van Koulil, Quinten; Douralidou, Despoina; Espadas, Irene; Benito Benito, Miguel; Anselmi, Carlo; et al. (Frontiers in Veterinary Science, 2025)
Occult tethered cord syndrome (OTCS) is poorly documented in dogs. This retrospective multicenter study evaluated the clinical presentation, MRI findings, treatment outcomes, and prognostic factors in 30 dogs diagnosed with OTCS managed surgically (n = 11) or medically (n = 19). Novel clinical severity scoring and neurological grading systems were developed to assess prognostic utility. The median age at clinical onset was 11 months (range 2–65), with a median duration of clinical signs of 13 months (range 1–60). Pain/dysesthesia in the lumbosacral region/tail/pelvic limbs was the most common presenting complaint (97%), followed by pelvic limb gait abnormalities (70%), behavioral changes (67%), impaired physical activity (63%), and urinary/fecal incontinence (17%). Neurological deficits were present in 90% of dogs. MRI findings showed variability in conus medullaris and dural sac termination, with no physiological translocation detected in available dynamic studies. Electrodiagnostic abnormalities were identified in four of nine tested dogs (44%). Clinical severity scores strongly predicted response to medical treatment, with responders having significantly lower scores than non-responders (3.25 ± 2.09 vs. 7.78 ± 3.15, p < 0.001). Higher neurological grades (p = 0.006), presence of behavioral abnormalities (p = 0.045), and worsening clinical evolution prior to referral (p = 0.009) were also associated with poor medical therapy outcomes. Surgical intervention was significantly associated with full recovery (p = 0.015) and discontinuation of medical treatment (p = 0.023) at last follow-up (median: 9 months, range: 2–108). Three surgically treated dogs experienced partial relapse within 6 months, with two undergoing reintervention and improving postoperatively. This study highlights the clinical and MRI characteristics of canine OTCS, introduces novel prognostic factors, and supports surgical detethering as a key intervention for optimizing outcomes. Larger prospective studies are needed to validate these findings, refine the proposed scoring systems, and establish evidence-based guidelines for managing canine OTCS.